Drivers overtaking bicyclists. Professional briefing document. - Walker, Ian (My University, 2006)
The broschure summarizes the key results of a psychological study, which briefly are: When overtaking the test bicycle, drivers passed closer when the experimenter wore a helmet, was male or drove closer to the center of the lane.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Verkehrsunfall; Sicherheitsabstand; Überholen; Überholvorgang; Seitenabstand